Current status of canine dirofilariosis in an endemic area of western Spain. Issue 4 (3rd July 2017) - Diosdado, A.; Gómez, P.J.; González-Miguel, J.; Simón, F.; Morchón, R.
Abstract: Since dirofilariosis caused by Dirofilaria immitis is a vector-borne disease, its distribution depends on environmental conditions as well as demographic factors and the management of pets by humans. In the province of Salamanca (west-central Spain) the disease has been known for many years, appearing in an area with extensive irrigated crops along the Tormes river. Because recent demographic changes have occurred in this area, the present study has been carried out with the aim of monitoring the distribution and prevalence of the disease in the canine population of this area. For that purpose, 191 dogs were analysed through antigen and microfilaria tests and geo-referenced in a map. The overall prevalence was 5.8%, although the disease was only present in dogs from municipalities with irrigated crops in which the prevalence was 16.7%. These results indicate that D. immitis continues to be present in the province of Salamanca, and that it is associated with the presence of irrigation, but with a clear decrease in the prevalence. Causes of the decrease in prevalence, as well as the potential zoonotic risk, are discussed.